Diagnostic Value of a Carpal Tunnel Corticosteroid Injection in Patients with Negative Electrodiagnostic Studies - Katt, Brian M.; Imbergamo, Casey; Padua, Fortunato; Leider, Joseph; Fletcher, Daniel; Nakashian, Michael; Beredjiklian, Pedro K. (Journal of Hand and Microsurgery, 2020)
Introduction There is a known false negative rate when using electrodiagnostic studies (EDS) to diagnose carpal tunnel syndrome (CTS). This can pose a management dilemma for patients with signs and symptoms that correlate with CTS but normal EDS. While corticosteroid injection into the carpal tunnel has been used in this setting for diagnostic purposes, there is little data in the literature supporting this practice. The purpose of this study is to evaluate the prognostic value of a carpal tunnel corticosteroid injection in patients with a normal electrodiagnostic study but exhibiting signs and symptoms suggestive of carpal tunnel, who proceed with a carpal tunnel release.Materials and Methods The group included 34 patients presenting to an academic orthopedic practice over the years 2010 to 2019 who had negative EDS, a carpal tunnel corticosteroid injection, and a carpal tunnel release. One patient (2.9%), where the response to the corticosteroid injection was not documented, was excluded from the study, yielding a study cohort of 33 patients. Three patients had bilateral disease, yielding 36 hands for evaluation. Statistical analysis was performed using Chi-square analysis for nonparametric data.Results Thirty-two hands (88.9%) demonstrated complete or partial relief of neuropathic symptoms after the corticosteroid injection, while four (11.1%) did not experience any improvement. Thirty-one hands (86.1%) had symptom improvement following surgery, compared with five (13.9%) which did not. Of the 32 hands that demonstrated relief following the injection, 29 hands (90.6%) improved after surgery. Of the four hands that did not demonstrate relief after the injection, two (50%) improved after surgery. This difference was statistically significant (p = 0.03).Conclusion Patients diagnosed with a high index of suspicion for CTS do well with operative intervention despite a normal electrodiagnostic test if they have had a positive response to a preoperative injection. The injection can provide reassurance to both the patient and surgeon before proceeding to surgery. Although patients with a normal electrodiagnostic test and no response to cortisone can still do well with surgical intervention, the surgeon should carefully review both the history and physical examination as surgical success may decrease when both diagnostic tests are negative. Performing a corticosteroid injection is an additional diagnostic tool to consider in the management of patients with CTS and normal electrodiagnostic testing.
Keywords: carpal tunnel syndrome; electrodiagnostic; cortisone injection; nerve conduction studies; electromyography